FOREIGN EXPERIENCE IN UPBRINGING MORAL RESPONSIBILITY OF RURAL YOUTH - Ірина Сопівник; Руслан Сопівник (Ternopil Volodymyr Hnatiuk National Pedagogical University, 2014)
The article presents the analysis of upbringing moral responsibility of rural youth in a number of countries, like as in the USA, France, Poland, China and Russia. The corresponding experience has been generalized. Major problems and difficulties in implementation of moral education of young people have been pointed out. Among those are: spread of anti-social phenomena (violence, cruelty, consumerism, irresponsibility, alcoholism); decrease in positive educational influence of a family, school and religion; absence of equal opportunities for development. Upbringing of morally responsible youth in separate countries has been shown on several different levels, as on the national, regional, district and local one.